Association of Year-to-Year Lipid Variability With Risk of Cognitive Decline and Dementia in Community-Dwelling Older Adults - Zhou, Zhen; Moran, Chris; Murray, Anne M.; Zoungas, Sophia; Magnussen, Costan; Chong, Trevor T. -J.; Shah, Raj C.; Sheets, Kerry M.; Nelson, Mark; Zhu, Chao; Tonkin, Andrew M.; Talic, Stella; et al. (Ovid Technologies (Wolters Kluwer Health), 2025)
Background and Objectives
Lipid metabolism in older adults is affected by various factors including biological aging, functional decline, reduced physiologic reserve, and nutrient intake. The dysregulation of lipid metabolism could adversely affect brain health. This study investigated the association between year-to-year intraindividual lipid variability and subsequent risk of cognitive decline and dementia in community-dwelling older adults.
Methods
ASPirin in Reducing Events in the Elderly (ASPREE) was a randomized trial of aspirin, involving 19,114 participants aged 65 years and older from Australia and the United States who were free of dementia and major cognitive impairment. ASPREE-eXTension is the post-trial observational follow-up of participants, currently to a maximum of 11 years. This post hoc analysis included participants who had lipid levels measured at baseline and in years 1, 2, and 3. Year-to-year variability in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), and triglycerides over the first 3 years was quantified using variability independent of the mean. Individuals who initiated or discontinued lipid-lowering therapy during this period were excluded. Multivariable Cox proportional hazards regression was used to analyze associations with incident dementia, adjudicated by expert panels, and cognitive impairment with no dementia (CIND) confirmed by a battery of cognitive tests, occurring after year 3. A linear mixed model was used for assessing the association with changes in 4 cognitive function domains, including global, memory, processing speed, verbal fluency, and a composite score from baseline to the end of follow-up.
Results
The analysis included 9,846 individuals (median [interquartile range] age: 73.9 [71.7–77.3] years, 54.9% female). 509 incident dementia and 1,760 CIND events were recorded over a median follow-up of 5.8 and 5.4 years after variability assessment. The hazard ratios (95% CI) comparing the highest and lowest quartiles of TC and LDL-c variability were 1.60 (1.23–2.08) and 1.48 (1.15–1.91) for dementia and 1.23 (1.08–1.41) and 1.27 (1.11–1.46) for CIND. Higher TC and LDL-c variability was also associated with a faster decline in global cognition, episodic memory, psychomotor speed, and the composite score (all p < 0.001). No strong evidence was found for an association of HDL-c and triglyceride variability with dementia and cognitive change.
Discussion
Tracking variability of TC and LDL-c may serve as a novel biomarker of incident dementia and cognitive decline in older adults.